The imprisoned nonviolent drug offender: Specialized martyr or versatile career criminal? - Delisi, Matt (American journal of criminal justice, 2003)
Some observers oppose imprisoning nonviolent drug offenders because they view incarceration as costly and such persons as generally benign. The careercriminal literature has established that perpetrators, including drug violators, commit an array of offenses. The current study merges these debates using a sample of 500 arrested adults selected from an urban jail in the western United States. Drug offenders amassed a much more extensive arrest history than other suspects net the effects of age, race, sex, prison history, and arrest onset. Drug offenders are quite versatile and do not conform to the image of specialized violators who are nominally criminal.